Influence Of The Pedological Cover On The Floristic Composition Of The Djoumouna Peri-Urban Forest, Brazzaville (Congo) - KIMPOUNI, Victor; NZILA, Jean de Dieu; WATHA-NDOUDY, Noël; KIONGO-MBINGOU, Fulgence Arland; YALLO MOUHAMED, Salisou; KAMPE, Jean Pierre (European Journal of Applied Sciences, 2021)
The study of the relationship between soil cover and floristic composition is carried out in Brazzaville (Republic of Congo) in the Djoumouna peri-urban forest. The main objective is to understand the current distribution of taxa in relation to soil types and to predict the evolutionary trajectory of this woody formation. The experimental device was focused on 2.4 ha subdivided into 15 plots of 40 m x 40 m. The methodology integrates (i) the floristic inventory of woody plants of d1.30 ≥ 10 cm, the description of the undergrowth and the immediate environment of the pits; (ii) the opening of a soil pit in the centre of each of the plots and the description of the profiles. Soil analyses reveal three subclasses: yellow soils represent 45.83% of the soil cover, red soils (54.16%); and truncated soils (22.91%). The soils are generally ferrallitic, with a sandy-clay texture; a subangular polyhedral fragmentary structure at depth, lumpy and rounded at the surface; and high porosity in the surface horizons. The floristic inventory reveals 57 species for 47 genera and 22 families, the dominant ones being Euphorbiaceae (19%), Fabaceae (15.8%) and Rubiaceae (7%). The average rate of Shannon index, maximum diversity and equitability are respectively 2.34 ± 0.09; 2.56 ± 0.09 and 0.91 ± 0.01. Jaccard's similarity coefficient is ranging between 9 and 82%. Data from the biodiversity indices showed heterogeneity reflecting the existence of floristic facies. At the same time, this ecosystem with a high level of specific diversity is very poorly floristic. The mesh of the pedological cover and the floristic dominance shows a concordance under forest facies and soil type. The original forest facies would be accommodated in yellow soils, while the red and truncated soils would host the taxa markers of anthropization.